Asymmetric hydrogenation by RuCl2(R-Binap)(dmf)n encapsulated in silica-based nanoreactors. Issue 2 (16th May 2014) - Peng, Juan; Wang, Xuefeng; Zhang, Xiaoming; Bai, Shiyang; Zhao, Yaopeng; Li, Can; Yang, Qihua
Abstract : RuCl2 -( R -Binap)(dmf) n encapsulated in silica-based nanoreactors: a solid catalyst as a whole, but a homogeneous catalyst on the nanoscale. Abstract : The Noyori catalyst RuCl2 ( R -Binap)(dmf) n has been successfully encapsulated in C-FDU-12 by using the active chlorosilane Ph2 Cl2 Si as the silylating agent. 31 P-NMR results show that there is no strong interaction between the molecular catalyst and the solid support, thus the encapsulated molecular catalyst could move freely in the nanoreactor during the catalytic process. The solid catalyst exhibits high activity and enantioselectivity for the asymmetric hydrogenation of a series of β-keto esters due to the preserved intrinsic properties of RuCl2 ( R -Binap)(dmf) n encapsulated in the nanoreactor. The solid catalyst could be recycled by simple filtration and be reused at least four times.